Dynamic Brain Activity Following Auricular Point Acupressure in Chemotherapy-Induced Neuropathy: A Pilot Longitudinal Functional Magnetic Resonance Imaging Study. (February 2020) - Yeh, Chao Hsing; Caswell, Keenan; Pandiri, Sonaali; Sair, Haris; Lukkahatai, Nada; Campbell, Claudia M; Stearns, Vered; Van de Castle, Barbara; Perrin, Nancy; Smith, Thomas J; Saligan, Leorey N
Background: The objective of this study was to investigate the dynamic brain activity following auricular point acupressure (APA) in chemotherapy-induced neuropathy (CIN). Methods: Participants received 4 weeks of APA in an open-pilot trial with repeated observation. Along with the clinical self-reported CIN outcomes, objective outcomes were measured over the course of the treatment by physiological changes in pain sensory thresholds from quantitative sensory testing (QST) and repeated functional magnetic resonance imaging scans. Results: After 4 weeks of APA, participants had reported clinically significant improvements (ie, ≥30%) in a reduction of CIN symptoms (including pain, numbness, tingling, and stiffness) in lower extremity stiffness (32%), reduced foot sensitivity (13%), and higher pain threshold (13%). Across the 11 intrinsic brain networks examined, there was a trend toward significance of the connectivity of the basal ganglia network (BGN) to the salience network (SAL), which was decreased pre-APA versus immediate-APA (effect size [ES] = 1.04, P  = .07). The BGN also demonstrated decreased connectivity with the language network pre-APA versus delayed imaging post-APA (ES = −0.92, P  = .07). Furthermore, there was increased executive control network (ECN) and SAL within-network connectivity comparing pre-APA to delayed imaging post-APA, trending toward significance (ES = 0.41, P  = .09 and ES = 0.17, P  = .09, respectively). Conclusion: The changes in connectivity and activity within or between the ECN, SAL, and BGN from pre- to post-APA suggest ongoing alterations in brain functional connectivity following APA, particularly in the insula, anterior cingulate, and dorsolateral prefrontal cortices, which play significant roles in pain, memory, and cognitive function.